POST COVID-19: Digital Epistemology and Flexible Education in Digital Era - Chang López, Roberto Enrique (EDU REVIEW. International Education and Learning Review / Revista Internacional de Educación y Aprendizaje, 2022)
This essay presents a strategy on school innovations supported by ICTs, MOOCs, and the internet in pedagogies as well as in learning modalities during and after COVID-19. A review of the literature on educational systems and innovation in educational quality and epistemology of digital education is included. Therefore, the problem is to flexibly rethink the internal processes of the school, but also to develop technological skills for both teachers and students in the transition from the traditional epistemological model to the digital one.